Effect of vitamin D supplementation regimens on clinical outcomes in asthma: A systematic review - Donna Pratiwi; Ni Ketut Sumartini; I Wayan Weta; Agustinus I Wayan Harimawan (World Nutrition Journal, 2026)
Background: Vitamin D has immunomodulatory properties that may improve asthma outcomes; however, randomized controlled trials (RCTs) have reported inconsistent findings. Variations in supplementation regimens, particularly bolus versus non-bolus dosing, may contribute to these discrepancies. Objective: To systematically evaluate the effects of vitamin D supplementation on clinical outcomes in patients with asthma, with particular emphasis on dosing regimens. Methods: A systematic review was conducted according to PRISMA guidelines and registered in PROSPERO (CRD420261378116). PubMed, Scopus, and the Cochrane Library were searched for RCTs investigating vitamin D supplementation in asthma. Studies were categorized into non-bolus (daily or weekly) and bolus (high-dose intermittent) regimens. Primary outcomes included asthma exacerbations, lung function, and asthma control. Risk of bias was assessed using the Cochrane Risk of Bias 2 tool. Results: Six RCTs met the inclusion criteria. Non-bolus supplementation was more consistently associated with improved asthma control and modest improvements in lung function, whereas bolus regimens generally showed no significant clinical benefit. Limited benefits of bolus dosing were observed only among participants with severe vitamin D deficiency. Overall, the included studies demonstrated low risk of bias to some concerns. Conclusions: Vitamin D supplementation may improve asthma outcomes, but its effectiveness appears to depend on the dosing regimen. Regular non-bolus supplementation may provide greater clinical benefits than intermittent bolus dosing, particularly in individuals with vitamin D deficiency. Further high-quality RCTs are needed to confirm regimen-specific effects.